Rapamycin Attenuated Cardiac Hypertrophy Induced by Isoproterenol and Maintained Energy Homeostasis via Inhibiting NF-κB Activation - Xi Chen; Siyu Zeng; Jian Zou; Yanfang Chen; Zhongbao Yue; Ying Gao; Luankun Zhang; Weiwei Cao; Peiqing Liu (Mediators of Inflammation)
Rapamycin, also known as sirolimus, is an immunosuppressant drug used to prevent rejection organ (especially kidney) transplantation. However, little is known about the role of Rapa in cardiac hypertrophy induced by isoproterenol and its underlying mechanism. In this study, Rapa was administrated intraperitoneally for one week after the rat model of cardiac hypertrophy induced by isoproterenol established. Rapa was demonstrated to attenuate isoproterenol-induced cardiac hypertrophy, maintain the structure integrity and functional performance of mitochondria, and upregulate genes related to fatty acid metabolism in hypertrophied hearts. To further study the implication of NF-κB in the protective role of Rapa, cardiomyocytes were pretreated with TNF-α or transfected with siRNA against NF-κB/p65 subunit. It was revealed that the upregulation of extracellular circulating proinflammatory cytokines induced by isoproterenol was able to be reversed by Rapa, which was dependent on NF-κB pathway. Furthermore, the regression of cardiac hypertrophy and maintaining energy homeostasis by Rapa in cardiomyocytes may be attributed to the inactivation of NF-κB. Our results shed new light on mechanisms underlying the protective role of Rapa against cardiac hypertrophy induced by isoproterenol, suggesting that blocking proinflammatory response by Rapa might contribute to the maintenance of energy homeostasis during the progression of cardiac hypertrophy.